1999
DOI: 10.1002/(sici)1520-6416(199902)126:3<9::aid-eej2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Distribution arrester outages caused by lightning backflow current flowing from customer's facility into power distribution lines

Abstract: Direct lightning strokes are considered to be a main cause of damage to surge arresters on power distribution lines. Recently, lightning performance of distribution lines has been observed using still cameras, and lightning‐caused distribution outages on hilltop areas on the coast of the Sea of Japan have been investigated. This research has shown a possibility that lightning backflow current flowing from customer facilities into distribution lines causes damage to surge arresters on the distribution lines. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…distribution lines based on observation results using still cameras [5][6]: "If the frequency of lightning strokes to a building with ineffective grounding or to an ungrounded building is considerable, it is expected that the outage ratio of distribution line due to backflow currents would be considerable". Thus, there are various types of lightning overvoltage on distribution lines to be considered for analysis of lightning trouble as follows:…”
Section: Yokoyama Et Al Proposed a New Cause Of Lightning Trouble Onmentioning
confidence: 99%
See 1 more Smart Citation
“…distribution lines based on observation results using still cameras [5][6]: "If the frequency of lightning strokes to a building with ineffective grounding or to an ungrounded building is considerable, it is expected that the outage ratio of distribution line due to backflow currents would be considerable". Thus, there are various types of lightning overvoltage on distribution lines to be considered for analysis of lightning trouble as follows:…”
Section: Yokoyama Et Al Proposed a New Cause Of Lightning Trouble Onmentioning
confidence: 99%
“…Then, experimental results considering the surge characteristics of the surge arrester by the scale-model technique are described, and it is confirmed that the proposed factor is applicable to lightning surge analyses of surge arresters on power distribution lines. 6 T. IEE Japan, Vol. A semi-conductor device was used in Reference [10] because the residual voltage of the device is very low, and it is easy to handle.…”
Section: Yokoyama Et Al Proposed a New Cause Of Lightning Trouble Onmentioning
confidence: 99%
“…When the value of the lightning surge current invading a low voltage house wiring is predicted, referring to references [5], [6], and [7] almost all the ranges are considered to be covered if its target is set at approx. 1 kA.…”
mentioning
confidence: 99%